Single photon double and triple ionization of allene. Issue 2 (20th December 2021) - Ideböhn, Veronica; Sterling, Alistair J.; Wallner, Måns; Olsson, Emelie; Squibb, Richard J.; Miniotaite, Ugne; Forsmalm, Emma; Forsmalm, Malin; Stranges, Stefano; Dyke, John M.; Duarte, Fernanda; Eland, John H. D.; et al.
Abstract : Single photon double and triple ionization of allene is investigated using multi-particle coincidence spectroscopies. Key findings comprise supporting evidence for a previously proposed roaming mechanism in H3 + formation by double ionization. Abstract : Double and triple ionization of allene are investigated using electron–electron, ion–ion, electron–electron–ion and electron–electron–ion–ion (ee, ii, eei, eeii) coincidence spectroscopies at selected photon energies. The results provide supporting evidence for a previously proposed roaming mechanism in H3 + formation by double ionization. The lowest vertical double ionization energy is found to be 27.9 eV, while adiabatic double ionization is not accessed by vertical ionization at the neutral geometry. The triple ionization energy is found to be close to 50 eV in agreement with theoretical predictions. The doubly charged parent ion is stable up to about 2 eV above the threshold, after which dissociations by charge separation and by double charge retention occur with comparable intensities. Fragmentation to H + + C3 H3 + starts immediately above the threshold as a slow (metastable) decay with 130.5 ± 9.9 ns mean lifetime.